A Study on Augmented Reality Assisted Navigation App Using Machine Learning and Computer Vision - Dhokley, Waheeda; Syed, Asif; Tomar, Nitika; Patil, Riya (International Journal of Computer Sciences and Engineering, 2019)
Indoor navigation has become as important as outdoor navigation. Navigating in big, unknown indoor environments with static 2D maps is a challenge, especially when time is a critical factor. Here we try to present a solution to this problem through an augmented reality based indoor navigation application to assist people in navigating indoor environments, which runs on mobile devices like smartphones or tablets. The excellent computing capabilities in today’s high-end phones or smartphones in combination with their multiple sensors, such as Global Positioning System (GPS), motion sensors, camera, wireless receivers, will allow us to develop a system more advanced than any previous attempts for indoor navigation. The solution will utilize an indoor image based positioning system that takes advantage of smartphones augmented reality (AR) and inertial tracking. The system will have the capability of delivering continuous 3D positioning and orientation of the mobile device which makes it ideal for any navigational application.